A dictionary of symbols - Chevalier, Jean, 1906-1993.; Gheerbrant, Alain (London, England ; New York, N.Y., USA : Penguin Books, 1996)
This remarkable and wide-ranging book is an inventory of symbols and the symbolic imagination. The editors and their fifteen contributors are drawn from a variety of scholarly backgrounds-including anthropology, ethnology, psychotherapy and art history. This diversity of approach is responsible for the book's unique character, a reflection of the multiplicity of symbols and signs and the phenomenal range of possible interpretations they offer. This book draws together folklore, literary and artistic sources, and focuses on the symbolic dimension of every colour, number, sound, gesture, expression or character trait that has benefitted from symbolic interpretation. The conscious and unconscious minds are explored, desire and dreams are treated alongside the known and the chronicled. Extraordinary in its range and eclecticism, this dictionary was originally published in French as the Dictionnaire des Symboles, and it is regarded as the standard work on the subject.
Translation of: Dictionnaire des symboles.
Includes bibliographical references (p. [1150]-1174).
Keywords: French literataure -- Translations into English; Signs and symbols -- Dictionaries; Folklore -- Dictionaries; Mythology -- Dictionaries; Symbolism in folklore -- Dictionaries